Manual of INTERNAL FIXATION Techniques Recommended by the AO-ASIF Group - Müller, Maurice E. 1918-2009; Allgöwer, Martin 1917-2007; Schneider, R.; Willenegger, Hans 1910-1998 (Springer Berlin Heidelberg, 1992)
In the early 1950s, the pioneering work of Robert Danis on operative treatment of fractures was in danger of falling into oblivion. Maurice E. Milller, impressed and intrigued by his contacts with Danis, first critically applied internal fixation and immediate mobilization to some 80 patients and found the basic concept confirmed, but in need of further develop ment with regard to technology, clinical application, and scientific analysis. In 1958 he assembled a group of friends, general and orthopedic surgeons, willing to invest time and effort in helping to create the necessary armamentarium and to form a study group for clinical trials. This group was set up in the same year under the name Arbeitsgemein schaft fUr Osteosynthesefragen (AO), later on to be known in English-speaking countries as the Association for the Study of Internal Fixation (ASIF). The first report on operative treatment of fractures by Milller, Allgower, and Willeneg ger, published in 1963, stressed the advantages of early open reduction and internal fixa tion. This book, first published in German, amusingly lost an important part when trans lated into English. At the suggestion of worried American and English partners, a picture series showing the healing pattern of 188 tibial fractures operated on in Chur between December 20, 1961 and April 26, 1962 was left out